2008
DOI: 10.1038/gt.2008.126
|View full text |Cite
|
Sign up to set email alerts
|

Redox proteins thioredoxin 1 and thioredoxin 2 support retinal ganglion cell survival in experimental glaucoma

Abstract: We investigated the neuroprotective effect of thioredoxin 1 (Trx1) and thioredoxin 2 (Trx2) which play critical roles in the regulation of oxidative stress on retinal ganglion cells (RGCs) in a rat glaucoma model. Expression of Trx1 and Trx2 and Trx-interacting protein (Txnip) was observed in the RGC layer (GCL), nerve fiber layer and inner nuclear layer. Txnip-, Trx1-and Trx2-expressing cells in the GCL were primarily colocalized with RGCs. The increased Txnip protein level was observed 2 and 5 weeks after gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 48 publications
4
61
0
Order By: Relevance
“…In support, several studies demonstrated that restoring Trx activity can prevent RGC death and apoptosis in aging liver cells or cardiomyocytes. 11,[33][34][35] However, our study is the first one to demonstrate a causal role of peroxynitrite in increasing TXNIP expression, altering thioredoxin system and activating ASK-1 proapoptotic pathway leading to RGC death in NMDA model.…”
Section: Figure 5 Fetpps Blocked Activation Of P38 Mapk Apoptosis Pamentioning
confidence: 63%
“…In support, several studies demonstrated that restoring Trx activity can prevent RGC death and apoptosis in aging liver cells or cardiomyocytes. 11,[33][34][35] However, our study is the first one to demonstrate a causal role of peroxynitrite in increasing TXNIP expression, altering thioredoxin system and activating ASK-1 proapoptotic pathway leading to RGC death in NMDA model.…”
Section: Figure 5 Fetpps Blocked Activation Of P38 Mapk Apoptosis Pamentioning
confidence: 63%
“…[29][30][31] In resting cells, ASK1 constantly forms an inactive complex with thioredoxin, whereas upon stimulation, ASK1 is dissociated from thioredoxin and activated by conformational changes and covalent modifications.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 On the other hand, PB1, a novel phosphineborane complex, promotes RGC protection through the induction of BDNF and activation of the extracellular signal-regulated kinases 1/2, but not ASK1, signaling. 33 The identification of small-molecule compounds that mimic some of the beneficial effects of trophic factors is of clinical interest.…”
Section: Discussionmentioning
confidence: 99%
“…Feilchenfeld et al reported that increased nitrotyrosine (a footprint for oxidative injury) is present in blood vessels and astrocytes in the pre-laminar optic nerve head in human primary open-angle glaucoma than controls [5]. Current evidence points to the association between oxidative stress and ganglion cell death without IOP elevation, which may be the cause of NTG in vivo and in vitro [11][12][13][14][15]. Harada et al reported that in glutamate transporter knock-out mice, decreased glutathione, a major cellular antioxidant, may cause retinal ganglion cell apoptosis without IOP elevation [15].…”
Section: Introductionmentioning
confidence: 99%